Fragile X mental retardation protein is a Zika virus restriction factor that is antagonized by subgenomic flaviviral RNA - Soto-Acosta, Ruben; Xie, Xuping; Shan, Chao; Baker, Coleman K; Shi, Pei-Yong; Rossi, Shannan L; Garcia-Blanco, Mariano A; Bradrick, Shelton (eLife, 2018)
Subgenomic flaviviral RNA (sfRNA) accumulates during infection due to incomplete degradation of viral genomes and interacts with cellular proteins to promote infection. Here we identify host proteins that bind the Zika virus (ZIKV) sfRNA. We identified fragile X mental retardation protein (FMRP) as a ZIKV sfRNA-binding protein and confirmed this interaction in cultured cells and mouse testes. Depletion of FMRP elevated viral translation and enhanced ZIKV infection, indicating that FMRP is a ZIKV restriction factor. We further observed that an attenuated ZIKV strain compromised for sfRNA production was disproportionately stimulated by FMRP knockdown, suggesting that ZIKV sfRNA antagonizes FMRP activity. Importantly, ZIKV infection and expression of ZIKV sfRNA upregulated endogenous FMRP target genes in cell culture and ZIKV-infected mice. Together, our observations identify FMRP as a ZIKV restriction factor whose activity is antagonized by the sfRNA. Interaction between ZIKV and FMRP has significant implications for the pathogenesis of ZIKV infections.
Keywords: Zika virus; RNA-binding protein; translation